Wisata Halal Madura: Strategi Destinasi untuk Daya Saing Pasar Pariwisata pasca Pandemi Covid 19 - Faidal Faidal (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The purpose of this research is to conceptualize the competitiveness of Madura halal tourism village destinations, formulate strategies to manage halal tourism village destinations effectively to help management make policies and for practitioners to better understand the advantages and problems of halal tourism village destinations and the development of halal tourism in Madura. especially after the COVID-19 pandemic.Methods This research uses a mix method with triangulation (case study design and survey design). For qualitative, data were collected from a number of tourist village destinations through observation, in-depth interviews, and FGD methods.The competitiveness of Madura as a halal tourism village destination is based on 7 sub-variables including: tourist attractions, most of the respondents tend to state that they are in good condition. as well as from the aspect of accessibility, amenities and institutions, that overall, respondents tend to say they are ready. The accommodations available in Madura as a whole have implemented halal principles in their services. need commitment and consistency in working on halal tourism in Madura in order to be competitive with other tours.